2019
DOI: 10.32383/appdr/109201
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effects of Tribulus terrestris, Ashwagandha and N-acetylcysteine on liver fibrosis in carbon tetrachloride-induced rats

Abstract: Fibrosis, which develops during the progression of liver damage, is the previous stage of cirrhosis. Carbon tetrachloride is one of the most commonly used hepatic toxins in experimental animal models of liver fibrosis. It was investigated the hepatoprotective effects of Tribulus terrestris, Ashwagandha and N-acetylcysteine in an experimental model of liver fibrosis induced by carbon tetrachloride in this study. Fifty Wistar rats were divided into five groups of 10 each, as follows: 1) Control, 2) Carbon tetrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…25 Various studies have reported the presence of phenolics, flavonoids, and anthraquinones in the A racemosus, M pruriens, A pyrethrum, and T terrestris used to prepare the PHP as a trweatment of liver injury in current study. [26][27][28][29][30][31] The presence of these phytochemicals with proven antioxidant potential are responsible for the reversal of liver injury in current study. 32 Kidneys play a vital role in the excretion of toxins such as creatinine, uric acid, and urea.…”
Section: Discussionmentioning
confidence: 99%
“…25 Various studies have reported the presence of phenolics, flavonoids, and anthraquinones in the A racemosus, M pruriens, A pyrethrum, and T terrestris used to prepare the PHP as a trweatment of liver injury in current study. [26][27][28][29][30][31] The presence of these phytochemicals with proven antioxidant potential are responsible for the reversal of liver injury in current study. 32 Kidneys play a vital role in the excretion of toxins such as creatinine, uric acid, and urea.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, hepatoprotective effects of T. terrestris , Ashwagandha, and N-acetylcysteine were measured by Ref. [ 78 ], in the liver of Wistar rats that had undergone experimental fibrosis induced by carbon tetrachloride. Malondialdehyde, NF-kB, collagen 1, nuclear factor erythroid-2-related factor 2, and tumor necrosis factor all showed numerical declines in the treatment groups when compared to the control, but aspartate aminotransferase and alanine aminotransferase levels were unaffected.…”
Section: Phytopharmacological Activities/medicinal Propertiesmentioning
confidence: 99%